The simple discharge relations of surface tension and viscosity on the rectangular flat-crested slit weir / R. Jaafar - Jaafar, R. (2016)
It has been recently shown that a rectangular slit weir can be used effectively as discharge measurement at small flow rates. In this study, slit weir concept is extended to the flat-crested surface to measure the discharges of small flow rates at low weir heights. The purpose of this study is to find out the relations of surface tension and viscosity on the discharge of water flow over a contracted rectangular flat-crested slit weir. This study was carried out on nine different weir heights with 10 mm weir width and 4 mm weir crest thickness. The study shows that the discharge coefficient is dependent on Reynolds number R and Weber number W and the related equations can be used to estimate the discharges of water flow over a contracted rectangular flat-crested slit weir. The relative errors of the coefficient of discharge are good as they are within + 5%.